Epidemiology of cutaneous melanoma in Blumenau, Santa Catarina state, Brazil from 1980 to 2019 - Nilton Nasser; Joana Laurindo da Silva; Grazielle Corrêa (Anais Brasileiros de Dermatologia, 2023)
Abstract Background The incidence and mortality of melanoma have increased in the last years in the Caucasian population. This 40-year study of melanoma incidence in Blumenau-SC shows the impact of primary prevention on the decrease of mortality. Objectives To classify cutaneous melanomas and evaluate their incidence in Blumenau from 1980 to 2019. Methodology This retrospective, descriptive and cross-sectional study collected 2,336 histopathological examinations of individuals living in the city, considering sex, age, primary location, histopathological type, invasion level (Clark), and tumor thickness (Breslow). The crude coefficients of annual incidence rates were calculated using the number of melanomas and the population estimated by the Brazilian Institute of Geography and Statistics between 1980 and 2019. Results Melanoma incidence rates reached 44.26 cases/100,000 inhabitants/year and the rates by sex reached 52.87 in men and 46.73 cases in women per 100,000 inhabitants. The most affected age group was 70 years old and over, with 421 cases in men and 301 cases/100,000 inhabitants in women. Superficial spreading melanoma occurred in 64.5% of the cases, followed by nodular melanoma in 22.8%. Early diagnoses reached 1900% with Breslow < 0.5 mm. Study limitations This study only covers histopathological reports with definitive diagnoses of cutaneous melanoma; therefore, the data are underestimated, consequently resulting in lower rates than in reality. Conclusions The incidence of cutaneous melanoma has increased fivefold between 1980 and 2009 and early diagnosis increased as a result of health education and primary prevention.